1998
DOI: 10.1097/00007890-199805150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Should All Human Immunodeficiency Virus-Infected Patients With End-Stage Renal Disease Be Excluded From Transplantation?

Abstract: The great majority of U.S. renal transplant centers will not transplant kidneys to HIV-infected patients with end-stage renal disease, even if their infection is asymptomatic. However, advances in the management of HIV infection and a review of relevant ethical issues suggest that this approach should be reconsidered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 28 publications
0
54
0
3
Order By: Relevance
“…From 1987 to 1997, only 32 kidney transplants were performed in known HIV-seropositive recipients nationally, as reported to the United States Renal Data System (15). At the end of that time period, a survey of U.S. transplant centers revealed that 88% would not transplant a kidney into an asymptomatic HIV-infected patient who was otherwise a good candidate for transplantation (16). The relatively few transplants performed during this period did not reflect demand; from 1993 to 1997 over 3600 HIV-infected patients developed end-stage renal disease, most commonly from HIV-associated nephropathy (17).…”
Section: Discussionmentioning
confidence: 99%
“…From 1987 to 1997, only 32 kidney transplants were performed in known HIV-seropositive recipients nationally, as reported to the United States Renal Data System (15). At the end of that time period, a survey of U.S. transplant centers revealed that 88% would not transplant a kidney into an asymptomatic HIV-infected patient who was otherwise a good candidate for transplantation (16). The relatively few transplants performed during this period did not reflect demand; from 1993 to 1997 over 3600 HIV-infected patients developed end-stage renal disease, most commonly from HIV-associated nephropathy (17).…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of 148 United States transplant centers published in 1998, the majority of responding centers would not transplant kidney from deceased (88%) or living (91%) donors into HIV-infected patients. Most centers feared that transplantation in such patients would be harmful to the recipient, and some believed that it would be a waste of scarce donor organs [11] . However, recent studies have demonstrated that kidney transplantation in HIV positive patients with ESRD who are receiving ART is safe and effective.…”
Section: Infected Patientsmentioning
confidence: 99%
“…The 12-month survival rate among HIVþ patients who started haemodialysis before 1990 was 56% and increased to 74% among patients who started dialysis in 1999-2000 [3]. Although death rates among HIVþ and HIVÀ patients were similar [3], the overwhelming majority of transplant centres in the United States that were surveyed in 1998 would not consider cadaveric or living donor kidney transplantation for HIV patients [4]. This may reflect the worse outcomes observed in HIVþ kidney transplant recipients prior to HAART [5].…”
Section: Kidney Transplantationmentioning
confidence: 99%